New species of Hemiodus (ostariophysi, characiformes, hemiodontidae) from the Rio Tocantins, Brazil, with comments on color patterns and tooth shapes within the species and genus - Langeani, Francisco [UNESP] (My University, 1999)
A new hemiodontid species, Hemiodus tocantinensis, is described from the rio Tocantins, Amazon basin, Brazil. It is most closely related to H. ternezi and H. thayeria based on the presence of a dark longitudinal stripe extending from behind the eye or the opercle to the tip of lower caudal fin lobe but is distinguished by the possession of 51 to 58 perforated lateral line scales and an oblique dark blotch on the dorsal fin extending from its anterior distal portion through the middle basal portion of the fin. The evolution of color patterns and tooth shapes present in the Hemiodus species is commented.
Keywords: Hemiodus; Hemiodus ternezi; Hemiodus thayeria; Hemiodus tocantinensis